Antimicrobial Activity of Some Brown Algae from Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN; ERDUGAN, HUSEYIN; AYSEL, VEYSEL (Asian Journal of Chemistry, 2010)
In vitro antimicrobial screening of methanolic extracts obtained from 6 brown algae (Calpomenia peregrine (Sauvageau) Hamel, Halopteris scoparia (Linnaeus) Sauvageau, Padina pavonica (Linnaeus) Thivy, Cystoseria compressa (Esper) Gerloff et. Nizamuddin, Cladostephus spongiosus (Hudson) C.Agardh and Scytosiphon simplicissimus (Clemente) Cremades) (Heterokontophyta) collected from coast of Canakkale, Turkey, against Escherichia coli ATCC 11230, Staphylococcus aureus ATCC 6538P, Klebsiella pneumoniae UC57, Pseudomonas aeruginosa ATCC 27853, Proteus vulgaris ATCC 8427, Bacillus subtilis ATCC 6633, Mycobacterium smegmatis CCM 2067, Listeria monocytogenes ATCC 15313, Microccoccus luteus CCM 169, Candida albicans ATCC 10231, Rhodotorula rubra DSM 70403, Kluyveromyces fragilis ATCC 8608 and Cryptococcus neoformans ATCC 90112 was conducted in this study by disc diffusion method. Cystoseria compressa was the most active exhibiting a broad spectrum antimicrobial activity against each of the microorganims tested. Contrary to this, the lowest effect was observed for Calpomenia peregrine. The other algae species have moderate effects. The extracts showing good antimicrobial activity are undergoing further analysis to identify the active constituents.